P190 iPAD4 – improving paediatric airway documentation. (June 2019) - Donnelly, Peter; Perkins, Joanne
Abstract : Introduction and aims: Intubation outwith the theatre environment is associated with higer risks than in-theatre intubation. 1 Patients admitted to the paediatric intensive care unit (PICU) may also have airway abnormalities making intubation unpredictable. Staff should be aware of any previous procedural difficulties. This audit set out to improve documentation about the paediatric airway in PICU. Methods: A quality improvement project was performed in PICU over 24 months with progress being recorded using a predesigned proforma. This aimed to ascertain details regarding the patients airway and airway proceduralist. It was also recorded if the bedside nurse was aware of the documented grade of laryngoscopy. The following interventions were performed and subsequently re-audited 1: a new airway details box was added to the paper observation balance chart, 2: a new electronic system was implemented in the PICU to replace all paper charts, 3: a laminated 'cheat sheet' was placed at every bedspace displaying key airway details. A 20 chart snapshot audit was performed after each intervention. Results: Some areas of documentation have shown marked improvement over the audit cycles. Bedside nurse awareness of airway details showed marked improvement with 90–100% (previously 24–75%) being aware of the grade of laryngoscopy. 100% of nurses knew where to find details about previous intubations and the size and length of the endotracheal tube was documented in 100% of cases. Documentation of the ease of bag mask ventilation (BMV) remains largely unchanged with an initial documentation rate of 50%. This fell with the initial two interventions before improving back to 50% in the most recent re-audit. Another area of improvement was documentation of laryngoscopy grade improving across the audit cycles from 79% to 95%. Documentation of the grade of airway proceduralist and ease of intubation showed marked deterioration with the implementation of the electronic monitoring system (falling from 79–100% to 5–10%, and from 28–50% to 15% respectively. Discussion and conclusion: The interventions performed to date have had mixed results with many areas showing improvement in documentation. Implementation of a new electronic system has provided some challenges and will provide an opportunity for further quality improvement interventions. Bedside nurse awareness of essential airway details have shown marked improvement over the duration of this project. References: Bowles TM, et al. Out-of-theatre tracheal intubation: prospective multicentre study of clinical practice and adverse events. British Journal of Anaesthesia . 2011; 107(5): 687–92